Comprehensive treatment of dogs with chronic generalized periodontitis in remission - Khomyn, N. M.; m, A. R.; Tsisinska, S. V.; Pritsak, V. V.; Nazaruk, N. V.; Khomyn, M. M. (ЛНУВМ та БТ імені С. З. Ґжицького, 2020)
It is known that periodontal diseases are a significant part of dental diseases in dogs. Chronic generalized periodontitis deserves the most attention. The disease develops slowly, beginning without visible clinical signs, but later, a combination of certain favorable etiological factors can lead to the loss of the animal's teeth, indigestion, metabolism with serious consequences for the dog. Therefore, the search of the features of the disease and the development of tactics for effective treatment of periodontally ill animals is relevant for modern veterinary dentistry. The aim of the work was to study the features of the course of chronic generalized periodontitis in remission in dogs and to develop tactics for rational treatment of periodontally ill animals. For the study, two groups of animals with chronic generalized periodontitis were formed in remission with 5 dogs in each (control and experimental), selected on the principle of analogues in terms of age and nature of the pathological process. Searches have shown that in chronic generalized periodontitis in remission in dogs there is an increase in the number of pathogenic microflora in the biotopes of the oral cavity, increasing the activity of acid phosphatase, increasing the protein concentration by reducing the content of lysozyme in the oral fluid. It was found that the dogs of the experimental group, after removal of tartar and rehabilitation of the oral cavity, were treated by using to the gums of ceftriaxone, diluted in 1% lidocaine hydrochloride solution in combination with 30 % dimexid solution 1 time per day for 7 days, anfluron injecteed intramuscularly at the rate of 1 ml 1 time per day for 7 days and caforsen – 0.1 ml/kg per day for 4 weeks. The treatment contributed to the recovery of dogs for 10 days, which is 8 days faster than in the control group.
Keywords: dogs; teeth; periodontitis; пародонтит у собак